2020
DOI: 10.1186/s43074-020-00022-w
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum-ultraviolet photodetectors

Abstract: High-performance vacuum-ultraviolet (VUV) photodetectors are of great significance to space science, radiation monitoring, electronic industry and basic science. Due to the absolute advantages in VUV selective response and radiation resistance, ultra-wide bandgap semiconductors such as diamond, BN and AlN attract wide interest from researchers, and thus the researches on VUV photodetectors based on these emerging semiconductor materials have made considerable progress in the past 20 years. This paper takes ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
77
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(77 citation statements)
references
References 126 publications
(144 reference statements)
0
77
0
Order By: Relevance
“…Vacuum ultraviolet (VUV) photodetectors own great application prospects in space science, based on their ability to identify the radiation less than 200 nm [1][2][3][4][5]. In order to conduct efficient monitoring, the characteristics like small size and low power consumption, as well as the performance including high sensitivity, large switching ratio and good stability [6][7][8], are pursued.…”
Section: Introductionmentioning
confidence: 99%
“…Vacuum ultraviolet (VUV) photodetectors own great application prospects in space science, based on their ability to identify the radiation less than 200 nm [1][2][3][4][5]. In order to conduct efficient monitoring, the characteristics like small size and low power consumption, as well as the performance including high sensitivity, large switching ratio and good stability [6][7][8], are pursued.…”
Section: Introductionmentioning
confidence: 99%
“…As a pioneer, Kumar et al reported flexible SERS substrates with AgNPs on grating PDMS structures that combine LSP and surface plasmon polariton structures [73,74]. Compared with this successful work, the laser-treated area shows much more hybrid micro-/nano-structures formation in a simple, high-speed, large-area way [75][76][77][78][79][80]. The porous PTFE structures enhance the interaction time between exciting light and matter, leading to the incident light reflection enhancement using the PTFE structure's porosity, which is significant for performance improvement.…”
Section: Resultsmentioning
confidence: 99%
“…Broadly, there are three types of sensing mechanisms, namely photoconductive effect, photogating effect, and photovoltaic effect. [ 4,24,25,29,30 ] Each of these mechanisms is explained below.…”
Section: Fundamentals Of Photodetectorsmentioning
confidence: 99%
“…The UV PDs fabricated using newly emerging 2DLMs can find a wide range of applications in the fields of biology, healthcare, and space science, such as disinfecting bio‐agents, environment monitoring, biological imaging, UV dosimetry, UV astronomy, UV imaging, flame detection, water purification, chemical analysis, secure communication, early missile warning systems and space missions, to name a few. [ 20,21,23–28 ]…”
Section: Introductionmentioning
confidence: 99%